1984
DOI: 10.1152/ajpregu.1984.247.2.r335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osmotic pressure, glucose, and temperature on neurons in preoptic tissue slices

Abstract: The preoptic area contains thermosensitive, osmosensitive, and glucosensitive neurons, which have been implicated in thermal, osmotic, and metabolite regulations, respectively. In this study, rat preoptic tissue slices are used to examine the specificity of these neurons by determining their individual firing rate responses to thermal, osmotic, and glucose stimuli. Of the neurons classified according to thermosensitivity, 35% were warm sensitive, 10% were cold sensitive, and 55% were temperature insensitive. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 0 publications
1
52
0
Order By: Relevance
“…In another study, the effects of low (1 mM) glucose and hyperosmotic (4.5 mM NaCI or 9 mM mannitol) media were observed on firing rates and thermosensitivities of PO neurons in vitro. These perfusions affected onethird of the temperature-insensitive neurons and nearly half of the thermosensitive neurons, generally exciting warm-sensitive neurons and inhibiting cold-sensitive neurons [61].…”
Section: Effects Of Chemicals On Thermosensitive Neuronsmentioning
confidence: 98%
“…In another study, the effects of low (1 mM) glucose and hyperosmotic (4.5 mM NaCI or 9 mM mannitol) media were observed on firing rates and thermosensitivities of PO neurons in vitro. These perfusions affected onethird of the temperature-insensitive neurons and nearly half of the thermosensitive neurons, generally exciting warm-sensitive neurons and inhibiting cold-sensitive neurons [61].…”
Section: Effects Of Chemicals On Thermosensitive Neuronsmentioning
confidence: 98%
“…Subsets of thermosensitive neurons in MPO and MnPO responded to changes in osmolality as well as temperature (69,81). However, these studies were not performed under conditions of synaptic blockade, and thus, did not establish whether the MnPO and/or MPO neurons were inherently osmo-or temperature sensitive.…”
Section: Sites For Integration Of Temperature and Fluid Homeostasismentioning
confidence: 99%
“…WSN are typically investigated for their role in regulating fever or response to peripheral and local changes in temperature. However, electrophysiological studies and molecular characterization demonstrated that these specialized cells also respond to nutrient signals (2,(6)(7)(8)(9)(10). Nutrient homeostasis is likewise regulated centrally and primarily in the hypothalamus (11).…”
mentioning
confidence: 99%